Playing it safe? Staff and young people's views about play opportunities in residential care: practitioner review - Natasha Robinson (Scottish Journal of Residential Child Care)
The paper adds to the body of knowledge in this area. While it is not entirely novel, it clarifies much of the general feeling within residential child care about outdoor activities. By researching this area with proper ethical guidelines and asking a wide range of questions in a variety of units, it consolidates much of what we suppose to be true. At the present time my own unit is experiencing some of the issues raised with activities, risk assessments and budgetary constraints. Indeed there was a sense of déja vu, as I heard some of the same comments echoed in my own unit in the last week. This contributed to the sense that the paper ‘rings true’ for me and I am sure it would also do so for the staff team at my place of work. In terms of the writing style, I found the paper to be extremely accessible. I particularly liked the way it represented the views of young people in a way that is starting to become more common in residential child care but which can still be overlooked in research.